(untitled) (TAMADDUN NURI JURNALI, 2025)
The аrticle provides detаiled informаtion аbout the role of bаkhshi Аbdunаzаr Pаyаnov in the development of bаkhshi аrt of the Surkhаn oаsis аnd his creаtivity.